Vitamin E supplementation moderates salt-induced oxidation status in beef - Eylon Asido; Jonathan Shalev; Joseph Kanner; David E. Gerrard; Zvi Roth; Oren Tirosh (Meat Science, 2026)

Water volumes, heat flow, and solute discharge from Old Faithful Geyser eruptions, Yellowstone National Park, USA - Shaul Hurwitz; R. Blaine McCleskey; Maxwell L. Rudolph; Sara Peek; David A. Roth; Melissa Schott-Atkins; Michael Manga; Kiernan F. Folz Donahue; Mara H. Reed; Jefferson D.G. Hungerford (Journal of Volcanology and Geothermal Research, 2026)

Variability in Fecundity–Body Size Relationships for Atlantic Salmon Associated With Body Condition and Life History - Tara L. Imlay; Cindy Breau; Julien April; J. Brian Dempson; John Hayward; Jason LeBlanc; Jenny E. Reid; David Roth; Jamie T. Vallis; Travis E. Van Leeuwen; Laura K. Weir (Fisheries Management and Ecology, 2026)
While body size is the primary driver of fecundity, other factors may contribute to variation in these relationships. Anadromous populations of Atlantic salmon ( Salmo salar ) have diverse life histories, and fisheries management relies on accurate fecundity estimates. We used Bayesian hierarchical models to determine the relationship between fecundity and fork length, and other life‐history characteristics, for 25 spawning populations throughout Eastern Canada. Fecundity was best modeled at the river level, increased with body size and condition, and decreased with mean egg diameter. Fecundity was higher for individuals that spent fewer years in freshwater as juveniles, and for consecutive repeat spawners compared with first‐time (or maiden) spawners that spent 1 year in the ocean. Lastly, there was interannual variability in the fecundity–body size relationship. These relationships should be used in conjunction with data on recent changes in body size and/or life‐history traits of populations to inform stock management.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Aerosol Delivery of Polyelectrolyte Surfactant—Antimicrobial Nanoparticles to the Lungs - Yadiel Varela Soler; Amanda S. Padilla-López; Sughosha Rao; Leonardo Calderon; Gediminas Mainelis; Olga Garbuzenko; Tamara Minko; David I. Devore; Charles M. Roth (Pharmaceutical Research, 2026)
Background Lung infections affect over 80% of adults with cystic fibrosis, with Pseudomonas aeruginosa being a leading pathogen. Although antibiotics are frequently nebulized as standard treatments, the physicochemical environment of the diseased lung often limits their diffusion and overall effectiveness. Our previous studies showed polyelectrolyte surfactants (PS) to be a promising delivery system for cationic antimicrobials in vitro . This study seeks to expand that knowledge by evaluating their potential for nebulized delivery. Methods To achieve this, we evaluated their size and antimicrobial activity following nebulization; in vitro toxicity against epithelial cells and erythrocytes; and biodistribution and expression of inflammation markers following administration to healthy mice. Results The nanoparticle formulation exhibited a mucolytic effect on an artificial mucus model of cystic fibrosis mucus. Following nebulization, nanoparticles retained both their size and biological activity. Additionally, they displayed no observable toxicity in vitro against either human lung epithelial cells or erythrocytes; instead, epithelial cells treated with PS-based nanoparticles showed increased cell viability. Following administration of these formulations to mice via inhalation, over 70% of the recovered nanoparticles were retained in the lungs 24 h after treatment, with a small fraction being uniformly distributed to other tissues. A screen of key inflammatory cytokines revealed that inhalation treatment led to a slight increase of IL-6 in the liver and IL-18 in the spleen. These increases seem to be consistent with a minor inflammatory response. Conclusion Overall, the results suggest that PS are a promising nanotechnology for the pulmonary delivery of cationic drugs.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

Taking Health into Your Own Hands: Evaluating Patient and Provider Perspectives of Human Papillomavirus Self-Sampling for Cervical Cancer Screenings and Opportunities for Education - Stella Roth; Breanne Lott; Jerlin Garo; Jordan Allen; Sara Krivacsy; Emily Buttigieg; Jessica Atrio; Maria Young; David Cepeda; Brittany Miller; Amr Soliman (Journal of Cancer Education, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Understanding key mineral supply chain dynamics using economics‐informed material flow analysis and Bayesian optimization - John Ryter; Karan Bhuwalka; Michelena O'Rourke; Luca Montanelli; David Cohen‐Tanugi; Richard Roth; Elsa Olivetti (Journal of Industrial Ecology, 2024)
The low‐carbon energy transition requires significant increases in production for many mineral commodities. Understanding demand, technological requirements, and prices associated with this production increase requires understanding the supply chain dynamics of many minerals simultaneously, and via a consistent framework. A generalized economics‐informed material flow method, global materials modeling using Bayesian optimization, captures the market dynamics of key mineral commodities. The method relies only on a limited set of widely available historical data as input, enabling quantification of economic relationships (elasticities) for supply chain components where data are sparse, and relationships cannot be obtained via traditional statistical approaches. Building upon established material flow analysis (MFA) and economic modeling techniques, Bayesian optimization was applied to fit an economics‐informed MFA model to global historical demand, supply, and price for aluminum, copper, gold, lead, nickel, silver, iron, tin, and zinc. This approach enables estimates for the evolution of ore grades, mine costs, refining charges, sector‐specific demand, and scrap collection for each commodity. Economic relationships were quantified and compared with a database compiled from the literature, including 1333 values from 213 analyses across 65 publications. Discrepancies in methods and limited coverage make use of these parameters in modeling efforts difficult. This work provides a single, homogeneous, probabilistic approach to identifying economic relationships across mineral supply chains, with uncertainty quantification, a literature database for comparison, and a modeling framework in which to use them. This article met the requirements for a Gold‐Gold JIE data openness badge described at http://jie.click/badges .

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Trophic Structure and a Temporal Shift in Trophic Diversity of Mobile Consumers in a Subarctic Estuary - Jillian R. St. George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuaries and Coasts, 2024)
Quantifying trophic relationships within and between species in terms of trophic position, ontogeny and trophic diversity provides information on community-level structure and function. Little attention has been focused on examining the trophic structure and temporal changes of communities in freshwater-marine coupled systems in the subarctic and associated impacts of anthropogenic activity on trophic interactions. Therefore, the objective of this study was to quantify the trophic position of mobile consumers (15 species in total) within the lower Churchill River area (Churchill, Manitoba, Canada), examine trophic position variation in relation to ontogeny, and measure the trophic diversity of a fish assemblage before (1993–1995) and after (2019–2020) the installation of the Churchill River weir in the late 1990s. We used stable isotopes (δ 13 C and δ 15 N) to quantify individual and group-level variation in trophic position of thirteen fish species and two seal species and also assessed six community-level metrics of a three fish species assemblage between time periods. Overall, species that mainly foraged on freshwater resources occupied lower trophic positions than species that mainly consumed marine resources. Trophic position increased with fish age only in cisco, fourhorn sculpin, Greenland cod and northern pike. A temporal shift from a trophically diverse to a more trophically redundant fish assemblage occurred between 1993–1995 and 2019–2020. As a result, these predator species now play similar trophic roles. Information on the long-term change in trophic structure of this sub-Arctic estuarine system may help with understanding how anthropogenic activity and climate change have influenced the trophic diversity of a fish assemblage inhabiting this system.

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

High-speed scattered-light imaging for sizing respiratory droplets - Adrian Roth; David Frantz; Mehdi Stiti; Edouard Berrocal (Journal of Aerosol Science, 2023)

Habitat coupling dynamics of mobile consumers along a freshwater and marine resource gradient in a sub-Arctic estuarine system - Jillian R. St George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuarine, Coastal and Shelf Science, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Evaluation in a porcine wound model and long-term clinical assessment of an autologous heterogeneous skin construct used to close full-thickness wounds - Nicholas Baetz; Pratima Labroo; Marytheresa Ifediba; Devin Miller; Kendall Stauffer; Michael Sieverts; Jessie Nicodemus-Johnson; Eric Chan; Ian Robinson; James Miess; Stephanie Roth; Jenny Irvin; et al. (Tissue and Cell, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Extremely rapid, Lagrangian modeling of 2D flooding: A rivulet-based approach - W. Brent Daniel; Corinne Roth; Xue Li; Cindy Rakowski; Tim McPherson; David Judi (Environmental Modelling & Software, 2023)

Why are adaptive facades not widely used in practice? Identifying ecological and economical benefits with life cycle assessment - David Borschewski; Michael P. Voigt; Stefan Albrecht; Daniel Roth; Matthias Kreimeyer; Philip Leistner (Building and Environment, 2023)

Interactive soil moisture interface of multi-depth change over time - David Gallacher; Guy Roth; Alex McBratney (Computers and Electronics in Agriculture, 2023)

Polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) soil contamination in Lausanne, Switzerland: Combining pollution mapping and human exposure assessment for targeted risk management - David Vernez; Christelle Oltramare; Baptiste Sauvaget; Hélène Demougeot-Renard; Lothar Aicher; Nicolas Roth; Isabelle Rossi; Arianna Radaelli; Sylvain Lerch; Vincent Marolf; Aurélie Berthet (Environmental Pollution, 2023)

Demonstration of Reversible Dispersion in a Darcy-Scale Push-Pull Laboratory Experiment - Roseanna M. Neupauer; Eric J. Roth; John P. Crimaldi; David C. Mays; Lauren J. Sather (Transport in Porous Media, 2023)

Design and Evaluation of Coastal Web Atlases: Best Practices and Future Opportunities for Map Representation, Interaction, and Usability - David A. Hart; Timothy Prestby; Robert E. Roth (Coastal Management, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Implementation of a Medication for Addiction Treatment (MAT) and Linkage Program by Leveraging Community Partnerships and Medical Toxicology Expertise - Gillian A. Beauchamp; Lexis T. Laubach; Samantha B. Esposito; Ali Yazdanyar; Paige Roth; Priyanka Lauber; Jamie Allen; Nathan Boateng; Samantha Shaak; David B. Burmeister (Journal of Medical Toxicology, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Methods for Laser-Induced Fluorescence Imaging of Solute Plumes at the Darcy Scale in Quasi-Two-Dimensional, Refractive Index-Matched Porous Media - Eric J. Roth; David C. Mays; Roseanna M. Neupauer; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2021)

Characterization of PfiT / PfiA toxin–antitoxin system of Pseudomonas aeruginosa that affects cell elongation and prophage induction - Itzhak Zander; Ester Shmidov; Shira Roth; Yossi Ben‐David; Irit Shoval; Sivan Shoshani; Amos Danielli; Ehud Banin (Environmental Microbiology, 2020)
Summary Toxin–antitoxin (TA) systems are small genetic modules usually consisting of two elements—a toxin and an antitoxin. The abundance of TA systems among various bacterial strains may indicate an important evolutionary role. Pseudomonas aeruginosa , which can be found in a variety of niches in nature, is an opportunistic pathogen for various hosts. While P . aeruginosa strains are very versatile and diverse, only a few TA systems were characterized in this species. Here, we describe a newly characterized TA system in P . aeruginosa that is encoded within the filamentous Pf4 prophage. This system, named PfiT/PfiA, is a homologue of the ParE/YefM TA system. It is a type II TA system, in which the antitoxin is a protein that binds the toxic protein and eliminates the toxic effect. PfiT/PfiA carries several typical type II characteristics. Specifically, it constitutes two small genes expressed in a single operon, PfiT inhibits growth and PfiA eliminates this effect, PfiA binds PfiT, and PfiT expression results in elongated cells. Finally, we assigned a novel function to this TA system, where an imbalance between PfiT and PfiA, favouring the toxin, resulted in cell elongation and an increase in virion production.

Modeling the Supporting Ecosystem Services of Depressional Wetlands in Agricultural Landscapes - David M. Mushet; Cali L. Roth (Wetlands, 2020)
We explored how a geographic information system modeling approach could be used to quantify supporting ecosystem services related to the type, abundance, and distribution of landscape components. Specifically, we use the Integrated Valuation of Ecosystem Services and Tradeoffs model to quantify habitats that support amphibians and birds, floral resources that support pollinators, native-plant communities that support regional biodiversity, and above- and below-ground carbon stores in the Des Moines Lobe ecoregion of the U.S. We quantified services under two scenarios, one that represented the 2012 Des Moines Lobe landscape, and one that simulated the conversion to crop production of wetlands and surrounding uplands conserved under the USDA Agricultural Conservation Easement Program (ACEP). While ACEP easements only covered 0.35% of the ecoregion, preserved wetlands and grasslands provided for 19,020 ha of amphibian habitat, 21,462 ha of grassland-bird habitat, 18,798 ha of high-quality native wetland plants, and 27,882 ha of floral resources for pollinators. Additionally, ACEP protected lands stored 257,722 t of carbon that, if released, would result in costs in excess of 45-million USD. An integrated approach using results from a GIS-based model in combination with process-based model quantifications will facilitate more informed decisions related to ecosystem service tradeoffs.

Reassessing Potential for Exotic Larch in Northern United States - David I Maass; Lloyd C Irland; James L Anderson; Kenneth M Laustsen; Michael S Greenwood; Brian E Roth (Journal of Forestry, 2020)
Abstract Field measurements of operational plantations and research plots demonstrate that growth rates of exotic larches in unmanaged stands can exceed 12 m3 per hectare per year in Maine and elsewhere. This paper briefly reviews the recent history of exotic larch (Larix decidua, L. kaempferi, and L. × marschlinsii) in northeastern United States and Canada. Stands can be commercially thinned as early as 15 years; further thinnings add to significant volume accumulation, based on stand table projections. Genetic development of the hybrid (L. × marschlinsii) could yield additional volume. Even at current low stumpage values, exotic larch plantations offer positive returns at realistic discount rates. In map form, we report a current inventory of known trials and operational plantings across the Northern United States, including adjacent Canada.

Wall Effect Mitigation Techniques for Experiments with Planar Walls - Eric J. Roth; Roseanna M. Neupauer; David C. Mays; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2020)

Integration of sudden death syndrome resistance loci in the soybean genome - Hao-Xun Chang; Mitchell G. Roth; Dechun Wang; Silvia R. Cianzio; David A. Lightfoot; Glen L. Hartman; Martin I. Chilvers (Theoretical and Applied Genetics, 2018)

A model-based assay design to reproduce in vivo patterns of acute drug-induced toxicity - Lars Kuepfer; Olivia Clayton; Christoph Thiel; Henrik Cordes; Ramona Nudischer; Lars M. Blank; Vanessa Baier; Stephane Heymans; Florian Caiment; Adrian Roth; David A. Fluri; Jens M. Kelm; et al. (Archives of Toxicology, 2018)

Clinical profile of suvorexant for the treatment of insomnia over 3 months in women and men: subgroup analysis of pooled phase-3 data - W. Joseph Herring; Kathryn M. Connor; Ellen Snyder; Duane B. Snavely; Ying Zhang; Jill Hutzelmann; Deborah Matzura-Wolfe; Ruth M. Benca; Andrew D. Krystal; James K. Walsh; Christopher Lines; Thomas Roth; et al. (Psychopharmacology, 2017)

Carry-over effects and foraging ground dynamics of a major loggerhead breeding aggregation - Simona A. Ceriani; James D. Roth; Anton D. Tucker; Daniel R. Evans; David S. Addison; Christopher R. Sasso; Llewellyn M. Ehrhart; John F. Weishampel (Marine Biology, 2015)

Characterization of electrocardiogram changes throughout a marathon - Vanessa Franco; Clifton Callaway; David Salcido; Serina McEntire; Ronald Roth; David Hostler (European Journal of Applied Physiology, 2014)

A Simplified Approach for Simultaneous Measurements of Wavefront Velocity and Curvature in the Heart Using Activation Times - Nachaat Mazeh; David E. Haines; Matthew W. Kay; Bradley J. Roth (Cardiovascular Engineering and Technology, 2013)

Keeping the blood flowing—plasminogen activator genes and feeding behavior in vampire bats - Åsa Tellgren-Roth; Katharina Dittmar; Steven E. Massey; Cecilia Kemi; Christian Tellgren-Roth; Peter Savolainen; Leslie A. Lyons; David A. Liberles (The Science of Nature, 2009)

Complex Microsatellite Dynamics in the Myostatin Gene Within Ruminants - Åsa Tellgren-Roth; Grigory Kolesov; Ana M. Sifuentes-Rincón; David A. Liberles (Journal of Molecular Evolution, 2008)

Stromal-cell regulation of natural killer cell differentiation - Claude Roth; Carla Rothlin; Sylvain Riou; David H. Raulet; Greg Lemke (Journal of Molecular Medicine, 2007)

Pharmacokinetics in mice implanted with xenografted tumors after intravenous administration of tasidotin (ILX651) or its carboxylate metabolite - Peter L. Bonate; David Beyerlein; Jennifer Crawford; Stephanie Roth; Roy Krumbholz; Steve Schmid (The AAPS Journal, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

WAY-100635 is a potent dopamine D4 receptor agonist - Benjamin R. Chemel; Bryan L. Roth; Blaine Armbruster; Val J. Watts; David E. Nichols (Psychopharmacology, 2006)

Mycorrhized Ri-transformed roots facilitate in vitro inoculation of Cistus incanus with Tuber melanosporum - Yvonne Ventura; David Mills; Varda Kagan-Zur; Nurit Roth-Bejerano; Amnon Bustan (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Dose-dependent retrograde facilitation of verbal memory in healthy elderly after acute oral lorazepam administration - Nunzio Pomara; Thomas M. Facelle; Amy E. Roth; Lisa M. Willoughby; David J. Greenblatt; John J. Sidtis (Psychopharmacology, 2006)

Computer Technology Helps Family Forest Owners in Pennsylvania and Washington - Paul A. Roth; James C. Finley; Kevin W. Zobrist; David M. Baumgartner (Journal of Forestry, 2006)
The use of computer technology in managing family forestlands is increasing. Growth, treatment, and visualization models can facilitate better understanding and communication of sustainable forest management concepts. Learning to use these tools can be challenging, and the technology has not been widely adopted at the landowner level. The Landscape Management System and associated Inventory Wizard have made these technologies easier to use and more accessible to landowners. Programs in Pennsylvania and Washington are promoting the use of this system by family forest owners.

Prefrontal cortical involvement in phencyclidine-induced activation of the mesolimbic dopamine system: behavioral and neurochemical evidence - J. David Jentsch; A. Tran; Jane R. Taylor; Robert H. Roth (Psychopharmacology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)